Draft Five Year Plan 1978-83 Government of Manipur - Planning Commission (Planning Commission, 1978)
Manipur is a small State in the North Eastern region of India. It attained statehood on the 21st of January, 1972 prior, to which it was a Union Territory, administered directly by the Centre. The total area of the State is 22,356 Sq. Kms. 10% of which is in the valley and 90% in the hills. Manipur has a 502 Kms. long border with Nagaland, Assam and Mizoram and a 352 Kms. long international border with Burma. There are six administrative districts viz. Manipur Central District, Manipur North District, Manipur East District, Manipur West District, Manipur South District and Tengnoupal District The districts are further sub-divided into 25 sub-divisions. The 26 development blocks are coterminous with the sub divisions except in the case of Imphal West Sub-division where there are two development blocks.
Government of Manipur
Secretariat Planning Department
Keywords: General Review; Pattern of occupation; State Domestic product; Review of Earlier Plans; Communication; Education; Health; Agriculture; Minor Irrigation; Forest; Co-operation and Industry; Objectives Strategy & Proposed Investments; Infrastructure Development; Economic Development; Transport & Communication; Art and Culture; Statistics; Art of Culture; Trend of Growth of Population; State; Domestic Product; The Problem of Unemployment